Anticipated HIV stigma and delays in regular HIV testing behaviors among sexually-active young gay, bisexual, and other men who have sex with men and transgender women - Gamarel, Kristi E. (AIDS Behav, 2018)
Young gay, bisexual and other men who have sex with men (YGBMSM) and young transgender women are disproportionately affected by HIV/AIDS. The success of biomedical prevention strategies is predicated on regular HIV testing; however, there has been limited uptake of testing among YGBMSM and young transgender women. Anticipated HIV stigma—expecting rejection as a result of seroconversion- may serve as a significant barrier to testing. A cross-sectional sample of YGBMSM (n=719, 95.5%) and young transgender women (n = 33, 4.4%) ages 15 to 24 were recruited to participate in a one-time survey. Approximately one-third of youth had not tested within the last 6 months. In a multivariable model, anticipated HIV stigma and reporting a non-gay identity were associated with an increased odds of delaying regular HIV testing. Future research and interventions are warranted to address HIV stigma, in order to increase regular HIV testing among YGBMSM and transgender women.